LABOUR MOVEMENT IN CHINA - Otniel Christofer (Universitas Jenderal Ahmad Yani, 2019)
The aim of this article is to give an explanation related to the industrial relations in China. Industrial relations is a study that explores the power play between three actors: government, companies, and labour. Along with the increase of global production, labour become one of the key actors in defining a state's economy and has become a relevant political forces. China is one of many nations that relies heavily on it's labour to be the motor of their economy. In the last 3 decades, China have seen their Gross Domestic Product (GDP) reached almost 10% improvement, and it's one of the fastest improved GDP in the modern economy. This was caused by a change in China's economy to an open-door policy in the 1970s. With this policy in place, this brings chances to multinational corporations (MNCs) to expand their activities to China. In 2010, Honda as one of the MNCs in China were facing a strike from their labour. They demand an improvement on their income and a more representing union. The theory used to support this research is a theory called resource mobilization theory. The focus in this theory is the ability of a social movement to acquire resources and mobilize it to achieve their goals. In this case, is economics goals and a more representing union. The research question used in this article is